Physical Properties of Alfisols, Growth and Products of Hybrid Corn Affected by Organic and Inorganic Fertilizer - Syamsiyah, Jauhari; Minardi, Slamet; Herdiansyah, Ganjar; Cahyono, Ongko; Mentari, Fegi Cahya (Universitas Sebelas Maret, 2023)
The nutrients of plants and the physical condition of the soil must both be considered to increase corn productivity. The continuous use of inorganic fertilizer without manures will cause a decrease in the physical properties of the soil. Therefore, this study aims to obtain doses of organic fertilizer from cow manure and inorganic fertilizers namely urea, KCl and SP-36 that will give the best effect on the physical properties of Alfisols, growth and yield of hybrid corn. The experiment was carried out using the randomized complete block design (RCBD) with two factors namely organic and inorganic fertilizers. Each factor was given at four dosages: 1, ¾, ½ and ¼ of the standard dose each with three replications. Observation parameters include bulk and particle density, soil porosity, aggregate stability, root volume and fresh weight, plant height, as well as the weight of corn with and without husks. The results showed that organic and inorganic fertilizers significantly affected bulk density, soil porosity, aggregate stability, root fresh weight, root volume, as well as the weight of corn with and without husks. Additionally, treatment with 7.5 to 10 tons of organic fertilizer as well as ¼, ¾ and 1 dose of inorganic fertilizers produced the best effect on soil physical properties of Alfisols, growth and yield of hybrid corn, while the lowest results were obtained in the control treatment. This indicates that organic treatment can reduce the use of inorganic fertilizers between ¼ to ¾ of the standard dose.